THE ROLE OF ORGANIZATIONAL CITIZENSHIP BEHAVIOR AS MEDIATION VARIABLES BETWEEN ORGANIZATIONAL COMMITMENTS AND EMPLOYEE PERFORMANCE: EVIDENCE FROM THE HOSPITALITY INDUSTRY IN SURABAYA - Wijaya, Oscarius Yudhi Ari (Jurnal Aplikasi Manajemen, 2020)
To create hotel customer satisfaction, OCB is needed constantly so that employ- ees themselves have expectations that exceed customer expectations themselves. As such, employees should continue to conduct OCB so that customers are satisfied with the high quality services shown by hotel employees. Therefore, it can be assumed that OCB has a fairly close relationship with the challenges of the hospitality industry services, so the understanding of OCB and its antecedent variables is important for the functioning of hotels effectively and efficiently. The purpose of this study is to examine the effect of Organizational Citizenship Behavior (OCB) as a mediator between organizational commitmentand employee performance. The number of research samples is 144 employees of 3, 4 and 5 star hotels in Surabaya. Research data was collected through questionnaires and processed using SmartPLS software. Three findings generated from this study are that organizational commitment has a positive and significant effect on employee performance both directly and through OCB as mediation, and OCB itself also directly has a positive and significant effect on employee performance. The results of this study are also very significant in enriching the OCB research area because it provides a more meaningful OCB measurement framework in the service industry, with special emphasis on the hospitality industry especially in Surabaya. This is very important because OCB began to gain popularity in the hospitality discipline recently.